P87 Vascular Adhesion Protein-1 promotes increases in liver infiltrating CD4+ T cells and NKT cells and induction of fibrogenesis in steatohepatitis. (6th September 2011) - Claridge, L C; Weston, C J; Haughton, E L; Westerlund, N; Reynolds, G M; Lalor, P F; Tomlinson, J W; Smith, D J; Day, C P; Adams, D H
Abstract : Introduction: Vascular Adhesion Protein-1 (VAP-1) is an adhesion molecule and membrane-bound amine oxidase. Our group has previously demonstrated that VAP-1 is able to support lymphocyte recruitment across human hepatic sinusoidal endothelium in vitro. Soluble VAP-1 (sVAP-1) is released into the circulation from adipose tissue and the hepatic vascular bed, has insulin like effects and is capable of inducing and propagating oxidative stress. Aim: To investigate the role of VAP-1 in the progression of steatosis to steatohepatitis and cirrhosis. Method: Human hepatic VAP-1 expression was determined using immunofluorescent labelling and multicolour confocal microscopy. Serum sVAP-1 levels were measured by ELISA in 144 patients with histologically graded NAFLD and 74 controls matched for age and metabolic phenotype. Two murine models of steatohepatitis were studied; (1) a methionine choline deficient diet was administered for 6 weeks in wild-type (WT) mice, WT mice treated with anti-VAP-1 antibody, and VAP-1 null mice (n=6 per group), 2) A western lifestyle model incorporating high trans-fat diet and fructose supplemented drinking water was administered to WT and VAP-1 null mice for 6, 9 and 12 months (n=10 per group). Control animals remained on normal chow. Liver infiltrating lymphocytes were identified and quantified using flow cytometry. Fibrosis was assessed by immunohistochemistry and qRT-PCR for aSMA and collagen I. Results: (1) Human studies: We report increased hepatic expression of VAP-1 in NAFLD associated with elevated serum levels of sVAP-1 compared with controls (946±468 ng/ml vs 265±78 ng/ml, p<0.0001). Multiple regression modelling reveals sVAP-1 to be the best predictor of histological fibrosis in our cohort. We detected strong VAP-1 expression in fibrotic septa co-localised with activated liver myofibroblasts (aLMF). In vitro human aLMF expressed and released sVAP-1 which promoted lymphocyte migration through a novel H2 O2 -mediated enzyme-dependent mechanism. (2) Experimental steatohepatitis: VAP-1 null and/or antibody treated mice developed fewer inflammatory foci and delayed onset of fibrosis in two murine models of NASH. In both models there was a specific failure to expand the intrahepatic CD4+ and NKT cell populations in VAP-1 null mice compared with 2 to 3-fold increases in WT mice. Three WT animals developed hepatocellular carcinoma by 12 months in the western lifestyle model but no tumours were found in VAP-1 null mice. Conclusion: Our results implicate an important role for VAP-1 in steatohepatitis, in both humans and mice. The ability to target VAP-1 with antibodies or small molecule inhibitors makes it an attractive therapeutic target.